Community Empowerment of Catfish Farming Groups through Processed Product Diversification to Increase Product Value in Balangnipa Village - Makmur; Muh. Amar; Sofyang; Mochamad.Nurdin; Nurfadillah; Sitti Fatimah (www.amertainstitute.com, 2025)
Catfish farming represents a strategic community-based economic activity due to its relatively low production cost, high nutritional value, and adaptability to limited land through tarpaulin pond systems. However, many small-scale catfish farming groups remain constrained by limited technical knowledge, weak market access, and the absence of value-added product diversification. This community empowerment program aimed to enhance the capacity of the Bululasiai Catfish Farming Group in Balangnipa Village, Sinjai Regency, through integrated interventions focusing on cultivation improvement, processed product diversification, packaging, marketing, and business legality. The methodology employed participatory approaches, including field surveys, focus group discussions, training sessions, and continuous mentoring to identify key challenges and local potential. The program outcomes demonstrate a significant improvement in participants’ knowledge and skills related to sustainable catfish cultivation, processed product development such as catfish sticks and nuggets, and attractive packaging techniques. Furthermore, the initiative facilitated greater awareness of market-oriented production and compliance with business legality requirements, including Business Identification Numbers (NIB) and halal certification processes. The diversification of processed catfish products contributed to increased product value and expanded income opportunities for group members and their households. Overall, the program generated positive economic and social impacts, strengthened local entrepreneurial capacity, and provided a replicable model for empowering small-scale aquaculture communities through value-added processing and integrated market-oriented strategies.